Applications of Thermal Energy Storage in Solar Organic Rankine Cycles: A Comprehensive Review - Salem, Mohamed; Fahim Alavi, Morteza; Mahariq, Ibrahim; Accouche, Oussama; El Haj Assad, Mamdouh (Frontiers in Energy Research, 2021)
Organic Rankine Cycles (ORCs) are promising approaches for generating power from medium or low temperature heat sources. In this regard, ORCs can be used to indirectly produce power from solar energy. Due to intermittent nature of solar energy, storage unit should be coupled with solar ORCs to improve the output power and operating hours. In this article, studies on solar ORCs integrated with various types of storage units were reviewed; the main findings of such studies were extracted and provided. Based on the findings, several factors such as the temperature and pressure at the inlet of the turbine, as well as the operating condition affect the performance of solar ORCs with thermal storage unit just like the conventional ORCs. In addition, the optimum size of the storage unit in the solar ORCs was found to depend on the operating condition. From the financial perspective, it can be noted that the storage unit affects the corresponding indicators. Moreover, the improvement rate in the ORCs by applying storage units could be affected by the configuration of the system.